2021
DOI: 10.1088/1755-1315/902/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Addition of bidara leaves (Ziziphus spina – christi L.) in drinking water on production and mortality of broiler chickens

Abstract: The bidara plant is known as a plant that contains active ingredients and phytochemicals that have the benefit of stimulating physiological processes in the body to run well and have a healthy effect. This study aimed to determine the effect of giving bidara leaf extract on the production performance and mortality of broiler chickens. A total of 60 DOC broiler chickens were used in this study with an average body weight of 45 g which was divided into 4 treatments, including T0: control, T1: 10% bidara leaf ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In another study in broilers, Yusup et al ( 22 ) investigated the effects of different levels (10%, 15%, 20%) of bidara ( Zizyphus spina -christi L.) leaf extract in drinking water on production and mortality and reported that bidara leaf extract in drinking water increased body weight gain, final body weight, feed intake, and water consumption. In the same study, it was determined that this extract in drinking water improved feed conversion.…”
Section: Discussionmentioning
confidence: 99%
“…In another study in broilers, Yusup et al ( 22 ) investigated the effects of different levels (10%, 15%, 20%) of bidara ( Zizyphus spina -christi L.) leaf extract in drinking water on production and mortality and reported that bidara leaf extract in drinking water increased body weight gain, final body weight, feed intake, and water consumption. In the same study, it was determined that this extract in drinking water improved feed conversion.…”
Section: Discussionmentioning
confidence: 99%
“…It reveals that the addition of S atoms to ZnO can affect the particle size. This difference could be attributed to the presence of sulfur impurities, which may affect the crystal growth and hinder the aggregation of particles, resulting in smaller and more dispersed particles [10]. Changes in particle size and morphology are likely to affect the band gap energy [9].…”
Section: Xrd Analysismentioning
confidence: 99%
“…However, there is growing interest in exploring the potential of Bidara (Ziziphus mauritiana L.) plants due to their medicinal properties, numerous benefits, and easy cultivation in Indonesia. Bidara leaves are particularly rich in antioxidants and phenolic compounds [10]. In recent studies, bidara plant extract has been successfully employed as a stabilizing agent for synthesizing CuO nanoparticles, demonstrating its effectiveness as an environmentally friendly synthesis route compared to conventional chemical methods [11].…”
Section: Introductionmentioning
confidence: 99%
“…Early menache or first menstruation at a relatively young age (less than 12 years) is associated with an increased risk of cancer with an OR = 1.5 [8] Based on the evaluation results, the latest evidence relating to diet and cancer, some recommendations to prevent cancer include a diet with organic types of food, balanced and varied nutrition, and a diet to maintain a normal body mass index and an active lifestyle [9,10,11]. This preventive approach, if widely implemented by international agencies, governments, industry, health professionals, consumers, and consumer advocacy groups, could reduce the global incidence of cancer by 10-20% within 10-25 years [ 12,13] One of the plants that can prevent the growth of breast cancer is Ziziphus jujube (Rhamnaceae) bidara plant [ 14,15,16 ] . The bidara plant has many useful ingredients including protein, calcium, iron, magnesium, vitamins, active compounds such as flavonoids, carotenoids, alkaloids, phenols, quercetin, methyl esters, terpenoids, saponins, and so on [17,18,19,20].…”
Section: Literature Reviewmentioning
confidence: 99%